PENGKLASIFIKASIAN PENYAKIT HIPERTENSI MENGGUNAKAN METODE CHI-SQUARE AUTOMATIC INTERACTION DETECTION - Kharisma Dwi Wahyuni; Darnah Darnah; M Fathurahman (Jurnal Gaussian, 2025)
Data mining is a technology used as an automated tool in the decision-making with classification being one of its techniques. The Chi-square Automatic Interaction Detection method classifies data by dividing samples into groups based on certain criteria, displaying results in a tree diagram. This study aims to obtain related factors, classification results, and accuracy of hypertension status classification of visitors to the East Kalimantan Provincial Health Office stand at the 2023 Kaltim Expo in Samarinda City using the CHAD method. The study found that age and family history are factors related to hypertension status. Classification results showed 10 elderly visitors without a family history of hypertension (2 with hypertension, 8 without), 216 non-elderly visitors without a family history of hypertension (9 with hypertension, 207 without), 10 elderly visitors with a family history of hypertension (9 with hypertension, 1 without), and 117 non-elderly visitors with a family history of hypertension (36 with hypertension, 81 without). The accuracy of hypertension status classification using the CHAID method was 86%.